A new advanced approach to the design of combustion chambers in diesel engines. (5th May 2006) - De Risi, Arturo; Donateo, Teresa; Laforgia, Domenico
An innovative methodology aimed at reducing emissions and improving fuel consumption has been developed for the design of internal combustion engines. The method allows the design of new combustion chambers by means of a fully automated procedure based on computational fluid dynamics (CFD) simulations, genetic algorithms and clustering. Four different engine operating conditions, i.e. load and speed values, were considered in the design of the combustion chamber. The results of the optimisation were used to understand the effect of the five geometrical parameters on the mechanism of formations of soot and NOx by analysing the distribution of temperature and equivalence ratio within the optimised chambers.